Estudio de factibilidad para la implantación de una nueva línea de procesamiento de productos marinados de pavo en la empresa AVITALSA S.A. ubicada en la parroquia Tumbaco en el periodo 2015 - 2016 - Cárdenas Acosta, Lissett Consuelo (2016)
AVITALSA Poultry Company S.A. which at first under the name Asesores Asociados Livestock A.P.A. was created in 1995 address the growing needs of the domestic consumer birds, after 20 years of its establishment is now a solid company that seeks to satisfy its customers with new alternatives; prepared feasibility study is based on five pillars which are fundamentals extensive market research, technical, organizational, economic, financial, and environmental impact matrix. In conducting the market study determined potential customers within the POS DELI ANDINO, through surveys it was determined that it is feasible to implement a new product line marinated turkey ready to bake in the surveys was determined the customer's desire for a higher frequency of consumption having a 39.47% monthly frequency and a taste for dressing made of 63.16%. After you make the proper technical study is considered an area of 50 square meters to be an appropriate size for the cost-benefit balance, as labor is needed 5 people to all production and administration it is necessary.